(untitled) (Research, Society and Development, 2022)
The Brazilian Unified Health System offers networked care, including speech therapy services, which encompass both clinical and health promotion actions, involving the Quality of Life of users. The aim of this study was to analyze the Quality of Life of elderly people assisted in a speech therapy clinic linked to the Unified Health System. This is a descriptive and quantitative study, carried out between June 2018 and June 2019, with 105 elderly, who answered two instruments: the World Health Organization Questionnaire of Quality of Life (WHOQOL-bref), which contains 26 questions, divided into four domains: physical, psychological, social relations and environment; and a structured questionnaire, in order to raise the reasons for seeking speech therapy, and also sociodemographic aspects. The results show a greater prevalence of men (51.4%), between 70 and 79 years of age (48.6%), with Elementary School education (78.1%), who sought care for hearing problems (98.2%). Regarding Quality of Life, the psychological domain was better evaluated and the physical domain was the worst. No significant difference was found between age, gender, and level of education. The perception of Quality of Life was significantly better evaluated by the elderly than the perception about their own health. The elderly participants tend to focus on health based on their physical conditions, especially regarding the hearing loss associated with age, which can negatively interfere in their social relationships, although they have a good perception of their quality of life.